Retroperitoneal Ectopic Pregnancy Detected by CT: A Case Report - Sunjin Ryu; Chul-min Lee; Bo-Kyeong Kang; Mimi Kim (Journal of the Korean Society of Radiology, 2024)
Retroperitoneal ectopic pregnancy is a rare form of ectopic pregnancy. Owing to its rarity and nonspecific symptoms, diagnosing retroperitoneal ectopic pregnancy at the initial presentation poses a significant challenge. Typically, the diagnosis relies on non-radiation imaging modalities, such as ultrasonography and MRI, whereas CT is infrequently used. Herein, we report a rare case of a retroperitoneal ectopic pregnancy, which was diagnosed using CT.